Using Waste Ceramic Dust in Stabilization of Clay Soils - Saber, Saya Abdullah; Iravanian, Anoosheh (International Journal of Sustainable Construction Engineering and Technology, 2022)
A considerable amount of the globally produced ceramic goes to waste daily. Ceramic wastes that are sent to the landfills have negative effects on soil, water, and the environment, as they contain aluminum, silica and iron oxide. The waste water leaching to the soil contains insoluble particular matter or heavy metals and could damage the plants. The air emission of the ceramic waste dumping process is also very high and it has negative effect on environment and human health by spreading dust. Using waste ceramic dust in soil stabilization could be for better disposal of such waste. The usage of natural resources can be minimized as well as prevent additional environmental burden and emissions. For this purpose, three local clay soil samples from Erbil in North-Iraq were gathered and the effects of addition of waste ceramic dust on mechanical properties of these samples were experimentally examined in two different grading sizes. The ceramic dust with particle sizes passing sieve No.40 and sieve No.10, in the proportion of 0, 5, and 10% percentages were used. The study showed that with an increase in ceramic dust percentages, liquid limit, plastic limit, plasticity index, optimum moisture content of the clay decreased. On the other hand maximum dry density, unconfined compressive strength and California bearing ratio increased. The study showed that addition of No.10 gradation ceramic dust results in higher improvement compared to the same amount of ceramic dust in No.40 size. The current work concludes that soil stabilized with the right type and ratio of ceramic dust could be suitable for a sustainable highway construction subgrade by reducing the design thickness and potentially be more economic